Aproximaciones a los estudios de las migraciones en Colombia. - Galeano Escucha, Luis Alberto (Revista Pensamiento Americano)
Objective: The objective of this article is to analyze the literature on migration phenomena in Colombia throughout its history, identifying factors that have influenced migration. Methodology: It addresses categories of analysis such as internal migration, forced displacement, immigration and diaspora, as well as the impact of colonization and rural-urban movements. First, a generic approach to the study of migrations is explored as an element of conceptual construction; secondly, a study of migration in Latin America and how Colombia escapes from the migratory flows of the late nineteenth and early twentieth centuries is made. Finally, the study of migration itself in Colombia is carried out, analyzing colonizations, rural-urban movements, forced displacement, immigration, diaspora and the factors of migratory relations with Venezuela. Conclusions: The need for interdisciplinarity in the study approaches is highlighted, considering socioeconomic, cultural and political aspects that affect population mobility. It is evident that Colombia has gone from being a sending country to a receiving country of migrants, especially in the context of the Venezuelan crisis.